How Analysis Scopus Database About Islamic Leadership Based on Quranic Studies Since 1987-2023? - Sulkhan Fajar Affani; Andri Nirwana AN; Fuadi (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of this study is to chart the evolution and direction of leadership research in Islam in papers indexed in the Scopus database. This study use bibliometric analysis tools to investigate all articles on Leadership in Islam indexed in the Scopus database between 1987 and 2023. The collected data was analyzed with Microsoft Excel and R/R-Studio. VOSviewer was used to conduct a visual study of the occurrence of keywords and document citations at the same time. The author discovered 330 papers that fit the function, subject, and criteria that were specified. The data revealed a 7.38% yearly growth rate. This study solely includes meta data from Scopus-indexed publications. This study did not take other national and international data borders into account. This study provides a quick summary of the literature available to Islamic Studies academics, as well as recommendations for further research.